2011
DOI: 10.21608/jfds.2011.81970
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of Low – Fat Cake

Abstract: Low-fat cake prepared by partial replacement of shortening with Maltodextrin or Simplesse were organoleptically evaluated and subjected to analysis for gross composition and caloric value. A nutrition experiment on rats was conducted to determine the effect of lowfat cake diet on growth parameters and serum lipid profile. The sensory evaluation results indicated that no significant difference (P≤ 0.05) was found among replacement treatments up to 50% replacement level and the full fat cake, and the panelists c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The lowest LDL-c was in rat groups fed on beef burgers with 2.5% chickpea (47.21 mg/dl) and with 10% chickpea comparing with negative and positive control. EL-Refai et al, (2011a), reported that TG, total cholesterol and LDL were significantly by fat replacers level and not affected by the fat replacer type.…”
Section: Serum Lipidmentioning
confidence: 96%
See 1 more Smart Citation
“…The lowest LDL-c was in rat groups fed on beef burgers with 2.5% chickpea (47.21 mg/dl) and with 10% chickpea comparing with negative and positive control. EL-Refai et al, (2011a), reported that TG, total cholesterol and LDL were significantly by fat replacers level and not affected by the fat replacer type.…”
Section: Serum Lipidmentioning
confidence: 96%
“…The rat groups fed on beef burger with chickpea (2.5, 5%) had the highest body weight gain (48.75 g). EL-Refai et al, (2011a) reported that neither fat replacer level non fat replacer type had significant effect on final weight, body weight gain (g) and feed efficiency raito of rats.…”
Section: Biological Evaluation Of Lowfat Beef Burgermentioning
confidence: 97%